Spirometric reference equations and lung function testing in adults from Southwestern Tanzania - R. Wenzel; E. Siyame; O. Ivanova; A. Bakuli; J. Lalashowi; F.C. Zekoll; M. Hoelscher; I. Sabi; A. Rachow; N.E. Ntinginya (IJTLD Open)
BACKGROUND: The increasing relevance of lung function testing in diagnosing and treating pulmonary diseases globally requires adequate spirometric reference equations. However, locally derived reference standards from African countries are widely missing. METHODS: This cross-sectional study was conducted in Southwestern Tanzania. Participants underwent a socio-demographic interview, anthropometric measurements and standardised spirometric lung function testing. Regression modelling was used to generate Tanzanian prediction equations for spirometry parameters forced vital capacity (FVC), forced expiratory volume in 1 sec (FEV1) and the FEV1/FVC ratio. RESULTS: Out of 400 recruited participants, 343 had usable spirometry results with respect to the American Thoracic Society (ATS)/European Respiratory Society (ERS) reproducibility and acceptability criteria. The mean age of participants was 32.65 years (SD 12.11), and 44,9% were females. Spirometric parameters increased with height but decreased with older age. The coefficients of our new prediction equations for spirometry parameters differed substantially from those of existing reference standards. CONCLUSION: This study provides prediction equations for spirometric lung function in a non-smoking Tanzanian population. The differences in existing equations underline the heterogeneity of locally derived reference equations in Africa and contribute insights and data to discussing global respiratory health care reference standards.